PERSONALITY TYPE AND TRANSLATION IDEOLOGY OF THE FIFTH SEMESTER STUDENTS AT ENGLISH LANGUGE EDUCATION IN UNIVERSITY OF HKBP NOMMENSEN MEDAN - Natly Julianty Pandiangan (Jurnal Suluh Pendidikan, 2020)
Translation and psychology are two different science, however, both of them can produce a great contribution in translation study. The data of the research are paired of translation and score MTBI. Paired of translation achieve from students' work and score of personality were from students' results in the form of a score. The design of this research is qualitative with interactive data analysis. This research figure out that the dominant personality type of translators is ESTJ (Extrovert, sensing, thinking and judging). The dominant personality type (ESTJ) produces a negative impact on translation ideology. In line with that, the weak ENFP and ISFJ type on translation ideology are negative. Contrary to that ESFP produced a positive impact since able to keep the balance between foreignization and domestication.